Northanger Abbey - Wadey, Maggie; Austen, Jane ([S.l.] : British Broadcasting Corporation)
Summary: Catherine Morland arrives in Bath bursting with freshness, intergrity and a passion for macabre Gothic novels. When the romantic Henry Tilney invites her to his ancestral home, Northanger Abbey, a dark mystery starts to unfold that makes her blood run cold. Are her fantasies coming true? What does the sinister General Tilney want from her and will the truth destroy her chance of love?
Cast : Peter Firth, Googie Withers, Robert Hardy
Keywords: Motion pictures; Love